2020
DOI: 10.1038/s41598-020-60436-1
|View full text |Cite
|
Sign up to set email alerts
|

Interspecies comparison of simultaneous thrombin and plasmin generation

Abstract: Animal models of hemostasis are often extrapolated to humans; however, only a few studies have compared coagulation and fibrinolysis across species. Simultaneous thrombin (TG) and plasmin (PG) generation is useful to assessing coagulation and fibrinolysis within the same sample. In this study, we performed simultaneous TG and PG analysis in blood plasma samples from humans and 6 species commonly evaluated in pre-clinical research. TG and PG were investigated in male and female donor platelet-poor plasmas (PPP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 42 publications
4
36
1
Order By: Relevance
“…Therefore, we believe that the good properties of GO and MXene nanoparticles improve the mechanical properties, antimicrobial performance and platelet adsorption of PHBV. There are also some limitations of this study, due to the differences between rabbit and human platelets [80][81][82]. The 95-99% antibacterial activity of PHBV-GO/MXene composite membranes is also not a remarkable antibacterial performance.…”
Section: Mechanical Property Antibacterial Activity and Platelet Adsorptionmentioning
confidence: 86%
“…Therefore, we believe that the good properties of GO and MXene nanoparticles improve the mechanical properties, antimicrobial performance and platelet adsorption of PHBV. There are also some limitations of this study, due to the differences between rabbit and human platelets [80][81][82]. The 95-99% antibacterial activity of PHBV-GO/MXene composite membranes is also not a remarkable antibacterial performance.…”
Section: Mechanical Property Antibacterial Activity and Platelet Adsorptionmentioning
confidence: 86%
“…As the reporting on the reason and timepoint of graft failure was incomplete in part of the papers, it would be too speculative to make the direct link. Nevertheless, important inter-species differences have previously been reported with respect to thrombogenicity, as well as regenerative potential 35 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Albeit that there were two different sites used, the latter more closely resembled the clinical situation in terms of thrombogenicity according to the authors 36 , as well as a review by Byrom et al 39 . Almost 30 years later, differences in hemostasis and thrombosis between preclinical animal models and humans are still extensively studied, because extrapolating the preclinical findings to humans still results in inaccurate predictions of the clinical scenario 37 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parameters for PG are peak concentration and average plasmin production rate before reaching the peak [ 85 ]. In an interspecies comparison, this group showed that TG and PG parameters from baboon and rhesus macaque plasma approximate that of humans, while other species (pigs, rats, and rabbits) differed from human [ 87 ].…”
Section: Assays That Measure Plasmin Generation Kineticsmentioning
confidence: 99%